Performance evaluation of a magnetic field measurement NDE technique using a model assisted probability of detection framework - Jarvis,R; Cawley,P; Nagy,P (NDT & E International, 2017)
Receiver Operating Characteristics (ROC) are a powerful tool used to evaluate the performance of NDE methods; however, the need to manufacture and scan many test pieces with realistic defects means that they are expensive and time-consuming to produce. Advances in computational power now mean that it is possible to use numerical models to greatly increase the efficiency of producing ROC for practical applications. A Model Assisted Probability of Detection (MAPOD) framework has been developed to predict the performance of magnetic field measurement NDE techniques. The MAPOD method is used to predict the performance of a promising new technique relying on the deflection of a current injected into a pipe at remote locations, and measurement of the resulting magnetic field perturbations due to defects. A significant proportion of pipes cannot be inspected by pigging methods, and external inspection often requires complete coating removal; therefore, an NDE method that functions outside pipe coatings and cladding is attractive. In this method, changes in the radial and axial components of the field are measured and attributed to defects, but a strong azimuthal component means that misalignment can give significant apparent radial and axial signals due to the azimuthal field apparently having a component in these directions. This requires that the second-order gradient of the magnetic field be measured to maximise sensitivity. Fluctuations in the sensitivity and orientation of the gradiometer during the scan are expected to determine the maximum sensitivity of the technique in most practical applications; however, the flexibility of the framework allows performance to be rapidly predicted and quantified for many test scenarios. Results suggest good detection performance for defects greater than 15% of the wall thickness (T = 7.1 mm) in a 6″ pipe with 2 A (200 A/m2) current injected when measuring above typical insulation thickness (25–50 mm).